Curcuma alismatifolia Gagnep.: asexual propagation, cultivation environment, and fertilization - Silva, Jeferson Antonio dos Santos; Santos, Carla Medianeira Girolleta dos; Taira, Tiago Ledesma; Araujo, André Luiz Xavier de; Soares, Jackeline Schultz; Ribeiro, Luan Marlon; Sorgato, José Carlos (Ornamental Horticulture, 2026)
he objective of this study is to evaluate the asexual production of Curcuma alismatifolia Gagnep. propagated either with or without reserve roots, cultivation environment, and fertilization. The experimental design was completely randomized in a 2 x 3 x 3 factorial design and six replications. The first factor was asexual propagation with and without reserve roots, the second factor was full sun or 30% or 60% of shaded environment and the third factor was fertilizer: 1 - without fertilization; 2 - 0.3 g of phosphorus (P) per pot or 3 - 0.3 g of phosphorus (P) + 12 g of Osmocote® (Plus 15-09-12) per pot. At the end of the crop cycle, we evaluated rhizomes as for length and diameter of the largest root, number of lateral buds, shoots and T-roots, diameter of reserve roots, and total fresh mass. Generally, rhizomes propagated without reserve roots performed comparably, and in some cases, superiorly, to those propagated with reserve roots for several evaluated variables. Full sun cultivation resulted in the lowest values for the evaluated variables. Fertilization with P + Osmocote® significantly enhanced the analyzed variables, demonstrating greater efficiency compared to mineral fertilization with P alone. We conclude that the propagation of C. alismatifolia can be carried out without reserve roots associated with fertilization of 0.3 g of phosphorus + 12 g of Osmocote® in an environment with a shading of 30%.